2020
DOI: 10.1186/s12894-020-00710-6
|View full text |Cite
|
Sign up to set email alerts
|

Ambient sulfur dioxide could have an impact on testicular volume from a observational study on a population of infertile male

Abstract: Background The effect of ambient pollutants on the male reproductive system is controversial. This retrospective study investigated the effect of environmental pollutants on male reproductive health. Methods Male patients with primary infertility (n = 282) were identified from a single center between January 2016 and December 2017. Patients were physically examined for the presence of varicocele and for the volume of both testicles. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Boggia et al [5], found a significantly lower percentage of motile sperm in workers exposed to traffic pollutants. Based on residential air pollution data, Chen et al [6], found that NOx exposure is a risk factor for reduced sperm concentration and motility. The adverse effect of NO2 exposure on total sperm count, concentration and normal sperm morphology was also described by Santi et al [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Boggia et al [5], found a significantly lower percentage of motile sperm in workers exposed to traffic pollutants. Based on residential air pollution data, Chen et al [6], found that NOx exposure is a risk factor for reduced sperm concentration and motility. The adverse effect of NO2 exposure on total sperm count, concentration and normal sperm morphology was also described by Santi et al [17].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that NO2 can also significantly impair central nervous system (CNS) function, including neurobehavioural development, in children [2,3]. Furthermore, multiple authors have confirmed the detrimental effects of NO2 exposure on sperm quality [4][5][6][7]. However, these results are still controversial because some authors failed to demonstrate an association between NO2 and sperm quality [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Oxidative stress and apoptosis are involved in mediating NO-induced infertility (Wu et al, 2022). Nitrogen Dioxide (NO2) and Sulfur dioxide (SO2) induced the expression of oxidative-stress-related genes and were negatively associated with sperm quality in a population of men with infertility (Chen et al, 2020). Both NO2 and SO2 concentrations emitted from incense burning were found to surpass the standards stated by US National Ambient Air Quality Standards (NAAQS) (Jetter et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Chinese scientists believe that particulate matter is considered a major pollutant, but nitrogen dioxide and ozone have recently shown a dominant trend [18]. In addition, exposure to NO 2 and SO 2 affect testicular function in men and lead to infertility in both sexes [19][20][21]. A significant association has been found between NO 2 , PM 2.5 , and SO 2 levels and hospital visits in children with respiratory diseases in China [22].…”
Section: Discussionmentioning
confidence: 99%